2017
DOI: 10.3390/nu9070785
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Amniotic Administration (Gallus gallus) of Cicer arietinum and Lens culinaris Prebiotics Extracts and Duck Egg White Peptides Affects Calcium Status and Intestinal Functionality

Abstract: Calcium (Ca) is one of the most abundant inorganic elements in the human body and has many important physiological roles. Prebiotics and bioactive peptides are two important substances used to promote calcium uptake. However, the difference in mechanisms of the calcium uptake from these two supplements is not clear. By using the Gallus gallus model and the intra-amniotic administration procedure, the aim of this study was to investigate whether Ca status, intestinal functionality, and health-promoting bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 63 publications
3
46
0
Order By: Relevance
“…Recently, the intra-amniotic administration model was used to evaluate the effects of prebiotics and duck egg white peptides on the promotion of calcium uptake [ 42 ]. It was found that the prebiotics and peptides increased the relative abundance of beneficial probiotics, the intestinal villus surface area, and goblet cell diameters, as well as regulated the calcium-related gene expressions.…”
Section: In Ovo Administration and Mineral Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the intra-amniotic administration model was used to evaluate the effects of prebiotics and duck egg white peptides on the promotion of calcium uptake [ 42 ]. It was found that the prebiotics and peptides increased the relative abundance of beneficial probiotics, the intestinal villus surface area, and goblet cell diameters, as well as regulated the calcium-related gene expressions.…”
Section: In Ovo Administration and Mineral Absorptionmentioning
confidence: 99%
“…Prebiotics from chickpea and lentil improve calcium bioavailability by promotion of gut beneficial prebiotics levels, the enlargement of gut villus surface area, and the improvement of BBM functionality. Duck egg white peptides promote calcium uptake through the reaction with calcium to act as calcium carriers and maintain gut health [ 42 ].…”
Section: In Ovo Administration and Mineral Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…serum, and all animal tissues was determined by nitric/perchloric acid digestion as previously described 38 followed by inductively coupled plasma-optical emission spectrometry (ICP-OES) using a Thermo iCAP 6500 series (Thermo Jarrell Ash Corp., Franklin, MA, USA). Fe-NA solution (Fe-NA); (6) 'Control' white flour extract (C WF); (7) 'Biofortified' white flour extract (B WF) and eggs were subsequently incubated for four days until hatch as described in 79,80 . Chicks were euthanized by CO 2 exposure after hatching and all tissues were collected.…”
Section: Micronutrient Analysis Micronutrient Concentration In Whitementioning
confidence: 99%
“…Lactobacillus, Bifidobacterium, Escherichia, and Clostridium density in intraamniotic administration treatment groups was determined as previously described 79 . In brief, cecal contents were homogenized with phosphate-buffered saline (PBS, 9 ml), centrifuged and the pellet resuspended in ethylenediaminetetraacetic acid (EDTA, 50 mM) and treated (37 °C, 45 min) with lysozyme (10 mg/mL, Sigma Aldrich CO., St. Louis, MO, USA).…”
Section: Microbial Population Analysismentioning
confidence: 99%